NETLab: An Online Laboratory Management System - Maiti, Ananda (International Journal of Online and Biomedical Engineering (iJOE), 2010)
Online hardware-based educational laboratories are increasingly being deployed in traditional on-campus as well as Web-based distance-learning courses around the world. An online laboratory generally will consist of several hardware-based remote experiments. However, one particular experiment can be performed at a time by an individual student or a group of students which require a careful scheduling of the experiments. For the proper implementation of an online laboratory an efficient laboratory management system (LMS) is thus essential. Also for an online laboratory, the students need to fully understand the experimental system setup and feel comfortable as in an actual laboratory environment which, however, can be effectively done by adding suitable videos and animations etc. Besides, the students should be able to run the remote experiments, extract, save and analyze the data and submit laboratory reports online. The front end of the laboratory management system should be made browser-based so that one can use the laboratory facility from anywhere. Also, for the teachers, the laboratory management system should include an online evaluation for the quiz/viva-voce, checking experimental data, grading of submitted laboratory reports and feedback for the students. In this paper, we describe the design and prototype implementation of an online laboratory management system (for use with shared hardware-based remote laboratory resources) which may be employed for running internet-based online laboratory courses for geographically dispersed Institutions.